Human Resource Performance Management Strategies to Enhance Employee Retention Through Job Satisfaction - Fatmawati, Diana; Nazmi, Izzuddin; Falah, Nurul (Lembaga Publikasi Ilmiah Nusantara, 2025)
Human resource (HR) performance management plays a strategic role in improving employee retention through job satisfaction. This study aims to analyze effective performance management strategies in creating a work environment that supports employee satisfaction, thus reducing turnover rates. The method used in this research is a quantitative approach with a survey conducted on employees from various industries. The findings of the study indicate that factors such as a fair performance evaluation system, performance-based rewards, training and development, and good organizational communication have a positive impact on job satisfaction. High job satisfaction directly affects employee loyalty and reduces the intention to change jobs. Therefore, organizations need to implement holistic performance management strategies that focus on employee well-being to improve workforce retention. The implications of this study emphasize the importance of managerial roles in creating effective and sustainable performance policies to maintain workforce stability in the long term.